Impact of entrepreneurship on Women’s Empowerment - Phulpoto, Nazar (Journal of Peace, Development and Communication, 2022)
Purpose: The major purpose of this study was to empirically analyze the impact of enterprise development and entrepreneur development on Women’s Empowerment. The present study was conducted in city Khairpur Mirs. Design/Methodology/Approach: The Data were collected through a questionnaire from the owners of small business setups. This includes those respondents who have a small level of work at their home or have a small business setup. It was seen that most of the respondents had a sewing machine, embroidery work and cultural handy crafts, etc. A sample size of 150 was randomly selected from the owners of small business setups. Cross-sectional survey Data were analyzed by using techniques of descriptive statistics, reliability, and regression analysis. Findings: The empirical analysis result shows that enterprise development and entrepreneur development have positive and significant impact on Women’s Empowerment. Women’s productive entrepreneur activities, particularly in small cities and rural areas , can provide them with economic empowerment and enable them to contribute more to the country’s overall growth. Women’s real and prospective contributions to development have long been acknowledged by many researchers, this researches findings also support the previous studies and have significant contribution in the area. Implications/Originality/Value: It is observed from the literature of various researchers as well as conclusion of this work, that if the women provided enough opportunities entrepreneurship activities, they become independent. They will take part in increasing GDP as well as developmental activities of the country. They become educated trained and a good decision maker. It will further improve the societal conditions of the region.